PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN KELAPA SAWIT DI BURSA EFEK INDONESIA - Khoesuma, Michael (Accounting Study Program, Universitas Ciputra Surabaya, 2022)
This study aims to examine the effect of Corporate Social Responsibility (CSR) on Financial Performance as measured by Return On Assets (ROA), Return On Equity (ROE) and Net Profit Margin (NPM). The population used in this study is the Sector Palm Oil Company listed on the Indonesia Stock Exchange in 2013-2017. Data collection used purposive sampling method which aims to determine the samples taken with certain criteria and objectives, deliberate data collection to be included in the criteria according to the research. Based on sample collection techniques obtained as many as 13 companies. The results found that 1) Corporate Social Responsibility (CSR) had a positive effect on ROA, 2) Corporate Social Responsibility (CSR) had a positive effect on ROE, 3) Corporate Social Responsibility (CSR) had a positive effect on NPM. This research has implications for palm oil company in improving its financial performance through CSR disclosure considering the higher the corporate social responsibility disclosure, the higher the company's financial performance. Keyword : Corporate Social Responsibility, Return On Asset, Return On Equity, Net Profit Margin.